1992
DOI: 10.1139/x92-060
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient cycling in Huntington Forest and Turkey Lakes deciduous stands: nitrogen and sulfur

Abstract: Biogeochemical cycling of S and N was quantified at two hardwood sites (Turkey Lakes watershed (TLW) and Huntington Forest (HF)) that have sugar maple (Acersaccharum Marsh.) as the major overstory component and are underlain by Spodosols (Podzols). TLW and HF are located in central Ontario (Canada) and the Adirondack Mountains of New York (U.S.A), respectively. Major differences between the TLW and HF sites included stand age (300 and 100 years for TLW and HF, respectively), age of dominant trees (150–300 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 0 publications
3
48
0
Order By: Relevance
“…The amounts of NO 3 --N accumulated on the resin in the Ae horizons increased as the amounts increased in the forest-floor horizon, suggesting that nitrate released in the organic layers is leached down to the Ae horizon. Mitchell et al (1992b) have reported that the dominant form of inorganic N leached through forest soils is NO 3 --N in hardwood forests. Rates of NH 4 + -N accumulation on the resin varied from 0.5 to 6 µg 10 cm -2 2 wk -1 for the Ae horizon and from 0.4 to 12 µg 10 cm -2 2 wk -1 for the forest-floor horizons.…”
Section: Spatial Patterns In Nitrogen and Phosphorus Supply Ratementioning
confidence: 99%
“…The amounts of NO 3 --N accumulated on the resin in the Ae horizons increased as the amounts increased in the forest-floor horizon, suggesting that nitrate released in the organic layers is leached down to the Ae horizon. Mitchell et al (1992b) have reported that the dominant form of inorganic N leached through forest soils is NO 3 --N in hardwood forests. Rates of NH 4 + -N accumulation on the resin varied from 0.5 to 6 µg 10 cm -2 2 wk -1 for the Ae horizon and from 0.4 to 12 µg 10 cm -2 2 wk -1 for the forest-floor horizons.…”
Section: Spatial Patterns In Nitrogen and Phosphorus Supply Ratementioning
confidence: 99%
“…An area in central Ontario, Canada not far from the study region has been reported to receive around 7 kg/ha per year through this flux (Mitchell et al, 1992). While this is lower than that reported for areas in New England (USA) (Bormann et al, 1977;Mitchell et al, 1992;Bormann and Likens, 1994), this is not surprising as the upper Lake States are more isolated from the industrial and automotive sources of N. Currently, NORTHWDS assumes atmospheric deposition of N is assumed to be a constant 7 kg/ha per year.…”
Section: Nitrogen Index and Biogeochemistry Plantavailable Nitrogen mentioning
confidence: 86%
“…However, the model-predicted root litter was greater than the measured values. At a hardwood plot adjacent to the Arbutus watershed, Mitchell et al (1991) estimated nitrogen litter fall (foliar plus woody) and net uptake (increment in bole and wood plus litter fall) to be 44Ð8 kg ha 1 year 1 and 44Ð7 kg ha 1 year 1 respectively. The estimates by Mitchell et al (1991) did not include the root litter, whereas the modelled litter fall and uptake fluxes of nitrogen (77Ð3 kg ha 1 year 1 and 81Ð9 kg ha 1 year 1 respectively) included the root litter and thus were higher than values reported by Mitchell et al (1991).…”
Section: Model Performancementioning
confidence: 99%
“…At a hardwood plot adjacent to the Arbutus watershed, Mitchell et al (1991) estimated nitrogen litter fall (foliar plus woody) and net uptake (increment in bole and wood plus litter fall) to be 44Ð8 kg ha 1 year 1 and 44Ð7 kg ha 1 year 1 respectively. The estimates by Mitchell et al (1991) did not include the root litter, whereas the modelled litter fall and uptake fluxes of nitrogen (77Ð3 kg ha 1 year 1 and 81Ð9 kg ha 1 year 1 respectively) included the root litter and thus were higher than values reported by Mitchell et al (1991). For the same reason, the modelled litter fall and uptake fluxes of sulphur (9Ð6 kg ha 1 year 1 and 7Ð2 kg ha 1 year 1 respectively) were greater than the values of 4Ð0 kg ha 1 year 1 and 5Ð3 kg ha 1 year 1 respectively obtained by Mitchell et al (1991).…”
Section: Model Performancementioning
confidence: 99%